Assessment of information and health habits of patients with diabetes mellitus - Zlatanović, Milena; Savić , Nikola; Lukić , Igor; Mitrović , Jelena; Jokić, Zoran; Ružičić , Dušan (PONS - medicinski časopis, 2021)
Objective: Diabetes mellitus is a chronic disease in which the body either does not produce or inadequately uses the hormone of the pancreas, insulin. Health education work with this population of patients is an important aspect of treatment and health care, it aims to change harmful health behavior and prevent complications. The aim of the research is to examine the information and health habits of patients with diabetes mellitus, to determine the presence of factors that can affect the worsening of the condition and lead to complications of the disease.Methods: The research was conducted according to the type of cross-sectional study. To collect data, a questionnaire for patients with diabetes mellitus was used, which the authors constructed for this research. The research was conducted in the population of patients with diabetes, in the period June-August 2018. At the General Hospital in Valjevo. The sample consisted of 110 respondents .Results: In the observed sample, almost 2/3 (63%) of the respondents are overweight, and almost 3/4 (74%) of the respondents regularly control their blood sugar values. More than 1/2 (56%) were educated for glycemic self-control, 70% were informed about signs of hyperglycemia, 87% were signs of hypoglycemia. More than 1/3 of respondents are exclusively on insulin therapy, 87% adhere to the therapeutic regimen, 87% of the subjects are trained for insulin self-application. 90% of respondents go to check-ups regularly, and 97% think that the information they receive from health workers is useful.Conclusion: Healthcare professionals of all profiles, primarily doctors and nurses, should continuously conduct health education work with people with diabetes. The largest number of patients in the observed sample were informed about their disease and hygienic dietary regime. In order to make the results even more encouraging, it is necessary to intensify health education work at all levels of health care. Key words: Diabetes mellitus, health habits, insulin.
Keywords: Diabetes mellitus, health habits, insulin